2022
DOI: 10.1002/prp2.989
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole sensitizes head and neck cancer cells to ionizing radiation by enhancing the production of reactive oxygen species

Abstract: Drug repositioning is an alternative process for drug development in cancer. Specifically, it is a strategy for the discovery of new antitumor drugs by screening previously approved clinical drugs. On the basis of this strategy, aripiprazole, an antipsychotic drug, was found to have anticancer activity. In this study, we investigated the radiosensitizing effects of aripiprazole on head and neck cancer cells at sublethal doses of ionizing radiation (IR) in vitro and in vivo. Treatment with aripiprazole suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In addition, <2.5 µM aripiprazole has no apoptotic effects on in vitro cancer cell lines [21,23,28]. However, combination treatment with low-dose aripiprazole increased apoptosis in radiation-treated head and neck cancer cell models [28]. Furthermore, this study showed that the sensitization mechanism of radiation + aripiprazole combined therapy mainly involved an increase in reactive oxygen species.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…In addition, <2.5 µM aripiprazole has no apoptotic effects on in vitro cancer cell lines [21,23,28]. However, combination treatment with low-dose aripiprazole increased apoptosis in radiation-treated head and neck cancer cell models [28]. Furthermore, this study showed that the sensitization mechanism of radiation + aripiprazole combined therapy mainly involved an increase in reactive oxygen species.…”
Section: Introductionmentioning
confidence: 69%
“…With the administration of aripiprazole at a low-dose of <2.5 µM, cancer cells have phenotypically normal proliferation and may grow similarly to untreated cancer cells. In addition, <2.5 µM aripiprazole has no apoptotic effects on in vitro cancer cell lines [21,23,28]. However, combination treatment with low-dose aripiprazole increased apoptosis in radiation-treated head and neck cancer cell models [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, aripiprazole was reported to have anticancer 33 and radio-sensitizing effects in various cancers, including head and neck cancer [34][35][36][37] . Kim et al argued that aripiprazole has antitumor effects via an important target molecule lined with Src, other than for psychotic purposes 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Olanzapine, an atypical antipsychotic, has been shown to increase the sensitivity of lung and pancreatic cancer cells to chemotherapeutic agents, including 5-fluorouracil, gemcitabine, and cisplatin (16). Aripiprazole, an atypical antipsychotic, has been identified as a radiosensitizer that boosts the therapeutic efficacy of radiation by upregulating the generation of reactive oxygen species (ROS) in head and neck cancer cells (17).…”
Section: Quetiapine Significantly Improves the Effectiveness Of Radio...mentioning
confidence: 99%